Pioglitazone improves the ability of learning and memory via activating ERK1/2 signaling pathway in the hippocampus of T2DM rats. (9th June 2017) - Gao, F.; Zang, L.; Wu, D.Y.; Li, Y.J.; Zhang, Q.; Wang, H.B.; Tian, G.L.; Mu, Y.M.
Highlights: This study explains the function of pioglitazone on the ability of learning and memory. The mechanism of pioglitazone relies on ERK1/2 signaling pathway activation. ERK1/2 signaling pathway activation is due to RKIP reduction. Abstract: OBJECTIVE: To explore the correlation between effect of PIO (pioglitazone, PIO) on learning as well as memory and ERK1/2 (extracellular signal regulated kinase 1/2, ERK1/2) pathway in T2DM (type 2 diabetes mellitus, T2DM) rats, further to elucidate the potential mechanism of PIO in improvement of learning and memory. METHODS: 12-week-old male SD rats (number of 10 per group) were randomly divided into control group (CON), T2DM group (DM) and T2DM +PIO group (DM + PG). Rats in DM and DM + PG groups were given high fat diet for 20 weeks, then treated with Streptozotocin (27 mg/kg) by intraperitoneal injection at 21week. After 72 h, the FBG (fasting blood glucose, FBG) was greater than 7.0 mmol/L can considered T2DM rats. DM + PG group was treated with PIO (10 mg·kg −1 ·d −1 ) by gavage daily. After Hyperinsulinemic-Euglycemic Clamp Study and Morris water maze test at 30-week, all of animals were sacrificed. The expressions of RKIP (Raf-1 kinase inhibitor protein, RKIP) and ERK1/2 in hippocampus were detected using Western Blot and real-time PCR. RESULTS: The FBG level: DM group (7.68 ± 0.54 mmol/L) was higher than CON group (5.35 ± 0.63 mmol/L) and DM + PG group (6.07 ± 0.84 mmol/L), the differences were considered statistically significant (P < 0.05). Hyperinsulinemic-Euglycemic Clamp Studies: GIR (glucose infusion rate, GIR) of DM group (21.02 ± 5.10 mg·kg −1 ·d −1 ) was less than CON group (27.64 ± 3.87 mg·kg −1 ·d −1 ) and DM + PG group (26.04 ±5.41 mg·kg −1 ·d −1 ), the differences were considered statistically significant (P < 0.05). Morris water maze training: The escape latencies and searching platform performance of DM group (24.54 ± 5.02s) decreased significantly compared with CON group (16.73 ± 4.02s) and DM + PG group (18.05 ± 4.12s) (P < 0.05). Changes of RKIP, ERK, p-ERK protein relative content in rat hippocampus: Compared with CON groupand DM + PG group, the relative content of RKIP in DM group remarkably increased (P < 0.01); ERK protein levels were not considered statistically significant among the three groups (P > 0.05); The relative content of p-ERK1/2 protein in CON group and DM + PG group rats dorsal were higher than those in group DM, the difference was considered statistically significant (P < 0.01). Changes in hippocampus of rat RKIP and ERK gene relative content: Compared with CON group and DM + PG group, levels of RKIP mRNA in DM group were significantly increased (P < 0.01); ERK mRNA levels were not considered statistically significant among the three groups (P>0.05). CONCLUSION: Activation of ERK1/2 signal transduction pathway via reducing RKIP in the hippocampus may be one of the mechanisms of PIO to improve the learning and memory of the T2DM rats.